AGRICULTURAL ENTERPRISES AND ECONOMIC GROWTH: A REGIONAL ANALYSIS IN THE REPUBLIC OF SERBIA - Dimitrijević, Miloš S; Vržina, Stefan; Lekovic, Miljan (Economics of Agriculture, 2020)
Since agriculture is the highly important economic activity in the Republic of Serbia, it is necessary to create an environment in which competitive agricultural enterprises will develop. However, regions in the Republic of Serbia considerably differ regarding the intensity of agricultural activity. This paper examines the impact of agricultural enterprises on the regions contribution to the gross domestic product (GDP) of the country in the period between 2010 and 2018. Activity of agricultural enterprises was observed using number of agricultural enterprises, number of employees in them, their turnover and gross value added. Random-Effects GLS regression showed that regions with higher agricultural activity contribute to the lesser extent to the GDP of the country. Research results are robust to changing sampling period and lagging independent variables. In this regard, several proposals have been recommended.